Gambaran Pemberian Makanan Baduta Stunting Usia 12-24 Bulan: Description of Parenting Patterns of Feeding of Stunted Infants Aged 12-24 Months - Murtadlo, Muhammad Hafidh; Meirina Dwi Larasati; Dian Luthfita Prasetya Muninggar; Ria Ambarwati (UNIVERSITAS NGUDI WALUYO, 2024)
Stunting is a chronic condition in toddlers that describes the inhibition of body growth due to long-term nutritional deficiencies. One of the factors that play a role in the occurrence of stunting is improper feeding parenting. Improper feeding parenting causes babies to not get enough nutrient intake so that baby growth is inhibited. To determine the parenting pattern of feeding stunted infants aged 12-24 months in the area of Public Health Center (Puskesmas) Tlogosari Wetan Semarang. This research was a descriptive study with a cross-sectional design. Subjects were taken using the total sampling method. The subjects used were 18 stunted infants aged 12-24 months with 3 infants included in the study exclusion. This study took data in the form of parenting practices in feeding, food diversity, and complementary feeding. Data on feeding parenting patterns were obtained by filling out questionnaires independently by respondents using a modified Child Feeding Questionnaire (CFQ) questionnaire based on the type of food, amount of food, and food schedule with a total of 15 questions. Food diversity data was obtained by direct interview method using the Individual Dietary Diversity Score (IDDS) form instrument through 24-hour Food Recall. Data on complementary feeding was obtained using a direct interview method using a questionnaire form. Data on complementary feeding was obtained by direct interview method using a questionnaire form based on the frequency given, food texture, and portion of complementary feeding to under-five children. Most of the respondents' feeding parenting was appropriate, complementary foods were given appropriately based on frequency and texture, while complementary foods were given inappropriately based on portion, and the subject's food diversity was high. Parenting style of feeding (15 respondents), appropriate complementary feeding based on frequency (12 subjects) and based on texture (13 subjects) and inappropriate complementary feeding based on portion (11 subjects), high food diversity (14 subjects). ABSTRAK Stunting merupakan kondisi kronis pada balita yang menggambarkan terhambatnya pertumbuhan tubuh karena kekurangan zat gizi dalam jangka panjang. Salah satu faktor yang berperan dalam terjadinya kejadian stunting adalah pola asuh pemberian makanan yang tidak tepat. Pola asuh pemberian makanan yang tidak tepat menyebabkan bayi tidak mendapatkan asupan zat gizi yang cukup sehingga pertumbuhan bayi menjadi terhambat. Mengetahui gambaran pola asuh pemberian makanan baduta stunting usia 12-24 bulan di wilayah kerja UPTD Puskesmas Tlogosari Wetan Semarang. Penelitian ini merupakan penelitian deskriptif dengan rancangan cross sectional. Pengambilan subjek menggunakan metode total sampling. Subjek yang digunakan yaitu 18 baduta stunting usia 12-24 bulan dengan 3 baduta masuk dalam eksklusi penelitian. Penelitian ini mengambil data berupa praktik pola asuh pemberian makanan, keragaman pangan, dan pemberian MPASI. Data pola asuh pemberian makanan diperoleh dengan cara pengisian kuesioner secara mandiri oleh responden menggunakan kuesioner Child Feeding Questionnaire (CFQ) yang telah dimodifikasi berdasarkan jenis makanan, jumlah makanan, dan jadwal makanan dengan jumlah soal sebanyak 15 pertanyaan. Data keragaman pangan diperoleh dengan metode wawancara secara langsung kepada responden menggunakan instrument formulir Individual Dietary Diversity Score (IDDS) melalui Food Recall 24 jam. Data pemberian MPASI diperoleh dengan metode wawancara secara langsung menggunakan formulir kuesioner berdasarkan frekuensi yang diberikan, tekstur makanan, dan porsi pemberian MPASI kepada baduta. Sebagian besar pola asuh pemberian makanan responden tepat, pemberian MPASI secara tepat berdasarkan frekuensi dan tekstur, sedangkan MPASI diberikan tidak tepat berdasarkan porsinya, dan keragaman pangan subjek tinggi. Pola asuh pemberian makanan tepat (15 responden), pemberian MPASI secara tepat berdasarkan frekuensi (12 subjek) dan berdasarkan tekstur (13 subjek) serta pemberian MPASI secara tidak tepat berdasarkan porsi (11 subjek), keragaman pangan tinggi (14 subjek).